Integrating Sensory, Emotional, and Social Customer Experiences to Drive Loyalty in Indonesia’s Coffee Shop Industry - Isana Sri Christina Meranga (Universitas Pelita Harapan, 2025)
This study examines the integrated influence of customer experience, encompassing sensory, emotional, and social on consumer repurchase intention coffee shop industry. The study's background is rooted in the shift from a product-centered to an experience-centered economy, as well as the rapid growth of the coffee shop market in Indonesia, which necessitates differentiation strategies for business sustainability. Using a quantitative approach with a cross-sectional study design, data were collected from 300 respondents in the Jabodetabek area through an online survey. Data analysis was conducted using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The results show that sensory, emotional, and social experiences have a direct and significant positive influence on repurchase intention. Furthermore, the study confirms a significant mediating role, where emotional and social experiences mediate the relationship between experience dimensions and repurchase intention. The most crucial finding is the confirmation of a sequential mediation model, where sensory experience influences repurchase intention through the sequential mediation of emotional and social experiences. Overall, this research provides empirical evidence that coffee shop businesses must holistically integrate sensory, emotional, and social elements into their strategies to build strong and sustainable customer loyalty.